When others show off my brand: self-brand association and conspicuous consumption. Issue 6 (25th November 2019) - Li, Jie; Guo, Shuojia; Zhang, Jonathan Z.; Sun, Liben
Abstract : Purpose: The purpose of this paper is to investigate the effect of conspicuous consumption on brand attitudes in the context of luxury brands market in China. Design/methodology/approach: Two studies are conducted to test three hypotheses. In Study 1, the authors examine the mediating effect of self-brand association (SBA) on the relationship between social class and conspicuous consumption ( H1 and H2 ); In Study 2, the authors examine the effect of observing others' conspicuous consumption on the observer's SBA (H3). Findings: Results show that SBA negatively mediates the relationship between social class and conspicuous consumption. Moreover, the negative effect on SBA of observing conspicuous brand usage varies by social class. Research limitations/implications: The current study focused on the principal linkage between social class, SBA and conspicuousness, and future research could examine the influence of different personality traits on luxury consumption or the existence of sub-types or variants of conspicuous brand users. Originality/value: The present study has important implications for luxury brand management, and provides rich insights to consumers' motivations that lead to distinctive luxury consumption behaviors.